(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to describe the planning, implementation, and improvement of narrative text writing skills using the Discovery Learning model in grade V of SD Negeri 03 Binuang Kampung Dalam, Kota Padang. This type of research is Classroom Action Research (CAR) with a qualitative and quantitative approach. The research is conducted in two cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of the research are the teacher and 28 students of grade V from SD Negeri 03 Binuang Kampung Dalam, Kota Padang, which consists of 11 male students and 17 female students. The research results indicate an improvement, in cycle I starting with the analysis of lesson planning modules: a) the lesson module showed an average percentage assessment of 89.58% (B) in cycle I, increased to 95.83% (SB) in cycle II, b) the implementation aspect of the teacher in cycle I achieved an average percentage of 82.82% (B) which increased to 96.87% (SB) in cycle II. Meanwhile, the implementation aspect of the students in cycle I obtained an average percentage of 82.82% (B) which increased to 96.87% (SB) in cycle II, c) the assessment of students’ knowledge learning outcomes in cycle I obtained an average of 60.71 (D) increased in cycle II to an average score of 84.64 (B). The assessment of learning outcomes in skills during Cycle I achieved an average score of 76.79 (C), which improved in Cycle II with an average score of 85.97 (B).